PELATIHAN PENGGUNAAN SOCIAL MEDIA BAGI KARYAWAN QALBY LAUNDRY - Shita, Rizky Tahara; Lauw, Li Hin; Diana, Anita; Santika, Reva Ragam; Tarigan, Fatmasari (Jurnal Abdimas Musi Charitas, 2025)
Purpose: Qalby Laundry is a micro, small, and medium enterprise operating in the laundry service sector since 2018, serving both individual and corporate customers. Although the business has adopted a website as part of its digital presence, the utilization of social media for marketing purposes has not been optimized. This community service activity aims to strengthen employees’ digital marketing capabilities through social media utilization in order to enhance business visibility and market penetration. Methodology: The activity was conducted through a training program combining theoretical explanation and hands on practice for Qalby Laundry employees. The training focused on introducing digital marketing concepts, selecting appropriate social media platforms based on target markets, and applying practical strategies for content creation and information dissemination. Findings: The training results indicate that participants gained new knowledge related to digital technology and online information dissemination through social media. Employees demonstrated an improved understanding of how social media platforms can be utilized for promotion, business expansion, and customer engagement in alignment with the characteristics of the target market. Practical Implications: The implementation of social media marketing enables Qalby Laundry to strengthen its promotional strategies, expand market reach, and enhance competitiveness in the digital era. Employees are better equipped to manage social media as an effective promotional tool that supports business sustainability. Originality Value: This program emphasizes employee empowerment as a key driver of digital transformation in micro and small enterprises. Rather than focusing solely on technology adoption, the activity builds practical digital marketing competence among employees to support long term business development.